PELATIHAN WRITING SKILL DALAM PENULISAN ARTIKEL ILMIAH BERSAMA PERSEKUTUAN PELAJAR RIRING-RUMAHSOAL AMBON (PRRA) - Makaruku, Nathalia Debby; Afdhal, Afdhal; Manuputty, Pieter Hendra; Almahdali, Humairah; Salampessy, Maryam (Universitas Pattimura, 2022)
Writing scientific papers is considered an important skill to be mastered by students. This relates to the writing of scientific papers as part of the tridharma of higher education. On the other hand, writing scientific papers can stimulate the growth of critical, analytical, and new ideas. However, many students complain that they lack ideas and can't find anything interesting to write about. In fact, many of them have to extend their study period because they have not finished their thesis. This is all constrained by the low ability of writing scientific papers among students. Therefore, the community service that the author does is training in writing skills (writing skills) in writing scientific papers at the Riring-Rumasalah Ambonese Student Association (PRRA). This training is carried out with a classical training pattern and focus group discussions in small groups. The results of this training show that the students' ability to write scientific articles is quite low, so they need further assistance